An Examination of the Writing Process in the Pre-Islamic Arab Period in the Pre-Islamic Arab History Book by Dr. Jawwad Ali - Rizki Putriani; Hibatullah Romdhoni; Ihya Salsabila (Yayasan Insan Mulia Bima, 2024)
The process of writing in pre-islamic Arabia had several periods and there were several factors that influenced the development of literary writing in Pre-Islamic Arabia, which had five separate periods at each time. This paper aims to examine more deeply the process of literary writing in pre-Islamic Arabia, which is studied through the book Pre-Islamic Arabic History written by Dr. Jawwad Ali. This study uses a literature study that explores Jahiliyyah Arabic literature from the perspective of social, religion and thoughts that influenced Jahiliyyah Arabic literature. The results of the study of Jahiliyyah Arabic literature are expected to increase the understanding of Arabic literature reviewers towards society and knowledge and aspirations about the culture of Jahiliyyah Arabic society from the perspective of historical and literary experiences